ANALISIS KANDUNGAN KLOROFIL PADA DAUN DAN KANTONG Nepenthes gracilis [Analysis of Chlorophyll in Lamina and Pitcher of Nepenthes gracilis] - Albar, Rahmat; Novitasari, Yuliana Diyah; Berlinda Paradisa, Yashanti; M, Des; Hilda Putri, Dwi; Chatri, Moralita Chatri; Solichatun, Solichatun; Wahyuni, Wahyuni (Berita Biologi, 2023)
Pitcher plants are plant species that have unique shapes. Nepenthes spp. in the feature has become an important issue about his developments in research on carnivorous plants and rare plants. Nepenthes spp. has been classified as a protected plant due to excessive exploitation, which can damage the place of origin. The research in this article focuses on analyzing the content of chlorophyll a, b, and carotenoid in leaves and pitchers of Nepenthes gracilis. Leaves and pitchers (fresh and dried) were extracted in 3 types of solvents (acetone, methanol, and DMSO). The samples were then analyzed with a UV-VIS spectrophotometer. The results showed that the leaf and pitcher samples had quite different results. The leaf sample showed higher results than the pitcher sample, which had a chlorophyll a (3.434a), chlorophyll b (1.311a), carotenoids (0.918a), and total chlorophyll (4.745a) content. The pitcher sample had a content of chlorophyll a (1.463b), b (0.642b), carotenoids (0.445b), and total chlorophyll (2.105b). The treatment of samples given various solvents such as DMSO, Acetone, and Ethanol showed insignificant results on the content of chlorophyll a, chlorophyll b, carotenoids, and total chlorophyll. The conclusion is that all solvents can be used to analyze pigment content. Keywords: Carnivorous plant, Nepenthes gracilis, Pigment Content, Extracted solvents